#TITLE_ALTERNATIVE# - PUTRI (NIM: 134061330 Pembimbing :Dr. Ir. Kadarsah Suryadi, DEA , ELDIANA
PT X as a security and defense equipment manufacturer has 4 business activities, consists of activities in the field of manufacturing, services, trades, and utilization of remaining capacity of the company. One of the activities is the investment activities undertaken by The Departement of Planning and Development, where the function is supported by the procurement aspects covering machinery and production equipment, materials and fuel, technology, information systems, and human resources. The investment activities certainly requires financial support and the optimal utility funds, so the investment decision making is a process that involves many aspects. Multi-criteria decision making is based on the consideration that the decision in the investment goods or services performed by PT X is a complex situation. Decision model is designed to be ued as investment decision support, so the company can make decision more structured and precise. Decision model created using the Analytic Hierarchy Process (AHP) model developed by Thomas L. Saaty in early 1970. AHP is a decision model based on a decision hierarchy by considering the priority of criteria or called weight. Hierarchy structure of development decision PT X consists of 6 levels: goal, strategic issues, criteria, sub criteria, rating scales, and the alternatives decision. This hierarchy structure is a general hierarchy structure in the AHP-based decision model with a small modification of alternative assesment section, using Five Point Rating Scale or Liberatore’s Scale. Sensitivity analysis is used to determine how much the influence of the weight change to changes in ranking criteria and the best alternatives that proposed by AHP. According to the result,it’s known that the decision model is not sensitive, so decision maker can put a high enough confidence to the result. This research proposes the addition of several criteria in considering alternatives selection. All criteria that currently evaluated and included in the hierarchy structure are gained from the investment evaluation document, discussion with expert, and can be assessed before the investment made. However, there are actually several other criteria should be considered and included in decision hierarchy, therefore the decision model could represent the real decision-making process